Studi Komparasi Konsep Pendidikan Akhlak Ibnu Miskawaih dalam Kitab Tahdzib Al-Akhlak dan Filsafat Etika Thomas Aquinas - Novanto, Muhammad Dwi (Hikmah, 2024)
Moral education is an important concept that has been studied by many famous figures, but today it is often only a theme of study without deep character cultivation. This study aims to analyse the comparison of the ethical philosophy of Thomas Aquinas and Ibn Miskawaih regarding moral education, especially in the book Tahdzib Al-Akhlak. Ibn Miskawaih is a Muslim philosopher who explores morals rationally and is known as the father of moral philosophy, while Thomas Aquinas is a Christian theologian philosopher who also discusses ethics a lot. Ethics and morals discuss good and bad human behaviour. This research is library research with qualitative methods using journals, books, and previous research. The findings show that moral education should refer to the thoughts of Ibn Miskawaih and Thomas Aquinas, although there are similarities and differences in their concepts, such as views on the human soul, ethical actions, happiness, friendship, and love. This research emphasises the importance of reviewing the concept of moral education rationally to form good character. This research has implications for the application in character building programmes, both in the context of formal and non-formal education, by taking the best aspects of the two philosophers to form individuals with noble character.